2018
DOI: 10.1055/s-0038-1639343
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preoperative Biliary and Pancreatic Drainage on Postoperative Pancreatic Fistula: A Retrospective Cohort Study

Abstract: Background  Surgeons and endoscopists welcome routine preoperative biliary drainage prior to pancreaticoduodenectomy despite evidence that it increases complications. Its effect on postoperative pancreatic fistula is variably reported in literature. Simultaneous biliary and pancreatic drainage is rarely performed for very selected indications and its effects on postoperative pancreatic fistula are largely unknown. Our aim was to analyze the same while eliminating confounding factors. Methods  Retrospective si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…Singhirunnusorn et al, proved a no significant difference in mild and major complications of patients with PBD (42% and 37%, respectively) in comparison to (35% and 32.8% respectively) in patients without PBD. They also reported no significant difference in hospital mortality, and each complication alone like biliary fistula, pancreatic fistula, WI, and reoperation (22,23). In contrast to our study with a significant difference in major complications, but maybe the definition of major complications that made these changes of results between the different studies.…”
Section: Discussion Discussioncontrasting
confidence: 80%
“…Singhirunnusorn et al, proved a no significant difference in mild and major complications of patients with PBD (42% and 37%, respectively) in comparison to (35% and 32.8% respectively) in patients without PBD. They also reported no significant difference in hospital mortality, and each complication alone like biliary fistula, pancreatic fistula, WI, and reoperation (22,23). In contrast to our study with a significant difference in major complications, but maybe the definition of major complications that made these changes of results between the different studies.…”
Section: Discussion Discussioncontrasting
confidence: 80%
“…There were few studies to evaluate the influence of pancreatic duct stenting during PBD on the complications of pancreaticoduodenectomy. A retrospective study by John et al in 2018 showed that simultaneous cholangiopancreatic duct drainage increased the incidence of postoperative pancreatic leakage [ 21 ]. This study enrolled only 5 cases of simultaneous cholangiopancreatic duct drainage, which was regarded as a rare event during data analysis and Firth logistic regression.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 36 unique series [9–44] from 24 institutes across India were identified after excluding 18 series [45–62] due to overlap of cases from the same author and institution. Figure 1 depicts the consort chart of the study methodology.…”
Section: Resultsmentioning
confidence: 99%
“…Incidence of post‐operative pancreatic fistula (POPF) in included studies ranged from 4 to 61.5%, with only 3 studies reporting POPF rates 41% [10], 54.3% [44] and 61.5% [20]. Apart from that, all other articles reported POPF incidence in the range of 4–15%, except six where the range was 20–35% [21, 28, 30, 37, 38, 43]. Only 19 out 36 studies reported incidence of clinically significant/relevant POPF with a range 0.6–18%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation